PENGEMBANGAN MODUL AJAR BERDIFERENSIASI DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI BILANGAN BULAT DI KELAS VII MTs NEGERI 1 PONTIANAK - Nurfadilah, Desi; Fadillah, Syarifah; Astuti, Reni (LPPM UM Metro, 2024)
The research method used in this research is development research or also known as Research and Development (R&D) research. The stages of developing teaching modules use the ADDIE model which stands for analysis, design, development, implementation and evaluation. Sampling used purposive sampling technique. The subjects of this research were class VII students at MTs Negeri 1 Pontianak. The instruments used were media and material expert validation sheets, teacher and student response questionnaires, and post-tests. The validity results reached an average of 81.2% including the